Stakeholders' Perspectives on Community‐Based Participatory Research to Enhance Mental Health Services. Issue 3 (23rd September 2014) - Case, Andrew D.; Byrd, Ronald; Claggett, Eddrena; DeVeaux, Sandra; Perkins, Reno; Huang, Cindy; Sernyak, Michael J.; Steiner, Jeanne L.; Cole, Robert; LaPaglia, Donna M.; Bailey, Margaret; Buchanan, Candace; et al.
Abstract: Historically, consumers of mental health services have not been given meaningful roles in research and change efforts related to the services they use. This is quickly changing as scholars and a growing number of funding bodies now call for greater consumer involvement in mental health services research and improvement. Amidst these calls, community‐based participatory research (CBPR) has emerged as an approach which holds unique promise for capitalizing on consumer involvement in mental health services research and change. Yet, there have been few discussions of the value added by this approach above and beyond that of traditional means of inquiry and enhancement in adult mental health services. The purpose of this paper is to add to this discussion an understanding of potential multilevel and multifaceted benefits associated with consumer‐involved CBPR. This is accomplished through presenting the first‐person accounts of four stakeholder groups who were part of a consumer‐involved CBPR project purposed to improve the services of a local community mental health center. We present these accounts with the hope that by illustrating the unique outcomes associated with CBPR, there will be invigorated interest in CBPR as a vehicle for consumer involvement in adult mental health services research and enhancement.